Learning Motivation, Family Environment and Learning Independence on Accounting Learning Outcomes - Astri, Sadana Aluh; Nurdin, Nurdin; Suroto, Suroto (Soedirman Economics Education Journal, 2023)
This study aims to determine the effect of learning motivation, family environment and also student learning independence on accounting learning outcomes in accounting students of SMK Muhammadiyah 2 Bandar Lampung. The study used a type of quantitative research with a descriptive verification method with an ex post facto and survey approach. The population in this study were students a majoring in accounting at SMK Muhammadiyah 2 Bandar Lampung. Determination of the sample in this study using nonprobability sampling with saturated sampling method. The results showed that there was a significant effect of learning motivation by 30.1%, family environment by 41.9% and learning independence by 22.9% and simultaneously influenced student accounting learning outcomes estimated at 31% of accounting learning outcomes.